Technical presentations - Courter, Sandy; Minix, Greg; Audio Visual Services (Madison : Audio Visual Services [production company] ; Kuala Lumpur : Visual Resources Training Solutions [distributor], 1992)
Explained the startegies of public speaking. To help in a better speaking to the public. Help to do a tecnical presentations.
lecture 1. Taming the butterflies - lecture 2. Preparation - lecture 3. Delivery - lecture 4. Quality review - lecture 5. Visuals : image power - lecture 6. Team presentations - lecture 7. Managing problem audience - lecture 8. Math talk - lecture 9. Humor - lecture 10. Teleconferencing - lecture 11. Interviewing technical people - lecture 12. Professional image and creadibility
Technical presentations : student handbook Spring, 1996 by Sandra Shaw Courter, The presentations kit : 10 steps for selling your ideas by Claudyne Wilder
Copy available in DVD format
Camera, Jannette Eng, Jeff Stevens, Tim Sorenson
Keywords: Business presentations; Public speaking; Communication in organizations